Trematode infection induced malformations in the common hourglass treefrogs - Rajakaruna, R.S.; Piyatissa, P.M.J.R.; Jayawardena, U.A.; Navaratne, A.N.; Amerasinghe, Priyanie H. (2008)
Reports on malformations in amphibians due to trematode infections prompted this study on an endemic frog species in Sri Lanka. The effect of an infection with a monostome-type cercaria is reported here. Ten days post-hatch, tadpoles (Gosner stage 27) of the common hourglass treefrog Polypedates cruciger (Anura: Ranidae), were exposed to a monostome-type cercaria, in a dose-dependent manner, under laboratory conditions. Malformations, survival and growth of the tadpoles were monitored for four treatments having different doses of cercariae (control=0, low=16, intermediate=32 and high=48). The severity and the number of malformations varied depending on the dose of the infection. A higher percentage (90%) of malformations was observed at higher doses of cercariae. Overall, malformations in the limbs, spine and skin pigmentation were common after parasite exposure. Survival declined with increasing doses of parasite infections, declining to 88% in the high treatment group, although not statistically significant. The growth rates of tadpoles as measured by weight and snout to vent length showed that exposed individuals were significantly smaller and had higher variance in growth compared with that of the controls. Thus, this trematode infection significantly affected the growth and induced severe malformations in P. cruciger, under laboratory conditions. Such malformed tadpoles and adults may face high predation under natural conditions. Here, we present the first empirical evidence of the effect of a trematode infection on the development of malformations, growth and survivorship in an endemic amphibian species in Sri Lanka.